2008
DOI: 10.1016/j.brainresbull.2008.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Activity of protein kinase C is important for 3α,5α-THP's actions at dopamine type 1-like and/or GABAA receptors in the ventral tegmental area for lordosis of rats

Abstract: In the ventral tegmental area, progestogens facilitate sexual receptivity of rodents via actions at dopamine type 1-like and/or γ-aminobutyric type A receptors and activation of downstream signal transduction molecules. In the present study, we investigated whether effects of progesterone's metabolite, 3α,5α-THP, to enhance lordosis via actions at these receptors in the ventral tegmental area requires phospholipase C-dependent protein kinase C. The objective of this study was to test the hypothesis that: if pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 77 publications
(115 reference statements)
0
12
0
Order By: Relevance
“…Allopregnanolone has been reported to activate PKA (Gonzalez-Flores et al, 2006; Mani et al, 2000) and MAPK (Etgen and Acosta-Martinez, 2003; Frye and Walf, 2008) and can increase Src kinase dependent Ca 2+ influx (Blackmore, 2008). Of relevance to the current findings is that allopregnanolone’s facilitation of lordosis can be blocked by PKC inhibitors (Gonzalez-Flores et al, 2006) or MAPK (Gonzalez-Flores et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Allopregnanolone has been reported to activate PKA (Gonzalez-Flores et al, 2006; Mani et al, 2000) and MAPK (Etgen and Acosta-Martinez, 2003; Frye and Walf, 2008) and can increase Src kinase dependent Ca 2+ influx (Blackmore, 2008). Of relevance to the current findings is that allopregnanolone’s facilitation of lordosis can be blocked by PKC inhibitors (Gonzalez-Flores et al, 2006) or MAPK (Gonzalez-Flores et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Progesterone also increases cAMP (Mani et al, 2000) and inhibition of PKA attenuates progesterone’s facilitation of lordosis behavior (Gonzalez-Flores et al, 2006). Lordosis-facilitating effects of allopregnanolone are less vulnerable to PKA inhibition (Gonzalez-Flores et al, 2006) but may, instead, involve PKC (Frye and Walf, 2008; Gonzalez-Flores et al, 2006) and/or potentiation of the GABAergic system (Frye et al, 2006) which has also been reported to attenuate inhibitory effects of 5-HT 1A receptors on lordosis behavior (Guptarak et al, 2004). Therefore, the collective evidence is consistent with the occurrence of considerable cross-talk among progesterone’s multiple signaling cascades and its ability to attenuate effects of mild stress on female rat sexual behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these signaling pathways (e.g. cAMP, PKC, PKA, MAPK, Src kinase) are also altered by allopregnanolone (Blackmore, 2008; Etgen and Acosta-Martinez, 2003; Frye and Walf, 2008; Gonzalez-Flores et al, 2006; Mani et al, 2000; Pluchino et al, 2006; Thomas and Pang, 2012) and allopregnanolone’s facilitation of lordosis can be blocked by PKC inhibitors (Gonzalez-Flores et al, 2006) or inhibitors of MAPK (Gonzalez-Flores et al, 2004). Therefore, allopregnanolone may indirectly activate intracellular progesterone by activation of intracellular signaling pathways.…”
Section: 0 Discussionmentioning
confidence: 99%
“…It has been recognized that in addition to steroid hormones, several neurotransmitters and neuropeptides influence female reproductive behavior in rodents. While the effects of acetylcholine, norepinephrine, serotonin (acting via 5-HT 2 , receptor subtype), DA (acting via receptor subtype D 1 ) and the neuropeptides GnRH, TRH, prolactin, oxytocin, substance P, and GABA A are considered facilitatory, serotonin (acting receptor subtype 5-HT 1A ), DA (acting through receptor subtype D 2 ), opioids, CRF, α-MSH, ACTH, β-endorphin, neuropeptide Y, cholecystokinin and glutamate are considered inhibitory on sexual behavior [26, 76, 93, 210, 250, 258]. …”
Section: Neurotransmitters In Female Reproductive Behaviormentioning
confidence: 99%